Gambaran Gejala Berdasarkan Skrining Abbreviated Conners Rating Scale pada Pasien Attention Deficit Hyperactivity Disorder Anak di RSUD Abdoel Wahab Sjahranie - Al-Ahmadi, Arina Fauziah Rahmah; Fitriany, Evi; Wardhana, Ahmad Wisnu (Jurnal Kesehatan Andalas, 2023)
Attention Deficit Hyperactivity Disorder (ADHD), or in Indonesian called Attention Deficit/Hyperactivity Disorder (GPPH), is a unique condition characterized by symptoms of inattention, hyperactivity, and impulsivity. Children with symptoms that lead to a diagnosis of ADHD need early detection using screening Abbreviated Conners Rating Scale(ACRS) Â so that earlier management can be carried out to prevent the emergence of other accompanying mental disorders in the future. Objective: To described symptoms based on ACRS screening in pediatric ADHD patients at Abdoel Wahab Sjahranie Hospital, Samarinda. Methods: This was a descriptive type using secondary data. The research data comes from the medical records of children with ADHD at the outpatient medical record installation at Abdoel Wahab Sjahranie Hospital Samarinda from 2019 until 2022 using the data collection method of total sampling. Sixty-seven patients met the inclusion criteria. Results: The analysis performed was univariate analysis.The results of this study found that most genders were male compared to girls, with a ratio of 3:1. The largest age group is preschool (3-6 years), at 76%. Screening for ACRS symptoms that received the most weight of 3, that is, it was always found was symptom number 1 at 54%. In the male sex, the ACRS symptom screening that gets the most value 3 is symptom number 1 by 56%. Meanwhile, in women, symptom number 6 is 53%.Keywords: Â ADHD, Symptoms, Detection of ADHD, Screening ACRS.